Desktop application connected to an ERP platform to manage the sales process, from design to order fulfillment - AHMED, Nedjm eddine; CHETRAUI, Nassim; Supervised:LOUNNAS, Bilal (University of m'sila, 2022)
ERP is an information system that makes it possible to manage and monitor on a daily basis all the information and operational services of a company. The subject presented is the Implementation of an ERP Solution, MELOUKI (MELOUKI Enterprise Resource Planning) The case study is to meet the need of a company with a national and also international activity. Our job is the development of an ERP solution at the company MELOUKI. This company wants to have an ERP solution to increase its efficiency to reduce its management costs, and the most
Keywords: Enterprise Resource Planning , Hisba-ERP